2011
DOI: 10.1007/s10654-011-9619-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of haemoglobin A1c and fasting plasma glucose for incident diabetes and implications for screening

Abstract: The aim of this analysis is to compare screening strategies with haemoglobin A(1c) (HbA(1c)), fasting plasma glucose (FPG) or combined measures in the identification of individuals at high risk for diabetes. Applying American Diabetes Association thresholds for FPG and HbA(1c) screening, 6,803 subjects free of diabetes were classified as non-diabetic, pre-diabetic and possibly diabetic by FPG (<100, 100-125 and >125 mg/dl) and HbA(1c) (<5.7, 5.7-6.4 and >6.4%). Hazard ratios, sensitivity and specificity were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 34 publications
(48 reference statements)
2
28
1
Order By: Relevance
“…In agreement with other studies [10,11,25], we showed in a previous analysis of the ESTHER data that the new HbA 1c -based prediabetes definition and IFG have a low proportion of overlap [12]. Nevertheless, individuals with IFG and those with HbA 1c -defined prediabetes showed a similarly increased burden of cardiovascular risk factors.…”
Section: Cardiovascular Risk Profilessupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with other studies [10,11,25], we showed in a previous analysis of the ESTHER data that the new HbA 1c -based prediabetes definition and IFG have a low proportion of overlap [12]. Nevertheless, individuals with IFG and those with HbA 1c -defined prediabetes showed a similarly increased burden of cardiovascular risk factors.…”
Section: Cardiovascular Risk Profilessupporting
confidence: 91%
“…Individuals with IFG, IGT and HbA 1c levels below 48 mmol/mol (6.5%) have been shown to be at increased risk for adverse cardiovascular outcomes [2,6,7], but estimates were mostly non-significant and studies comparing the cardiovascular risk of individuals with IFG or IGT with the new HbA 1c -defined prediabetes definition are sparse [8]. There is a need for detailed comparisons in large-scale cohorts because the overlap of prediabetes definitions is low [9][10][11][12]. The comparison of IFGand HbA 1c -defined prediabetes has the greatest relevance for clinical practice because the OGTT is unlikely to be used in primary prevention programmes because of its poor reproducibility, time requirement and costs [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Results of the EPIC-Potsdam Study also suggested that risk reclassification was improved by adding FPG (IDI 0.0553) or HbA 1c (IDI 0.0974) values using the prediction model by the German Diabetes Risk Score as a reference [14]. Recent prospective studies have examined the utility of introducing HbA 1c testing for predicting diabetes [15,16,[23][24][25][26][27], and some reports have described the development of models to predict future diabetes using blood variables including FPG and HbA 1c [15,25,29]. More recently and concomitantly with the preparation of this manuscript, a risk score that concurrently included measurements of FPG, HbA 1c and other biochemical markers was reported in a Korean population [40].…”
Section: Discussionmentioning
confidence: 99%
“…Introducing HbA 1c into a prediction model has been suggested to be effective in screening for future diabetes [14][15][16][22][23][24][25][26][27][28], and a few models to predict the development of diabetes have recently been developed that concurrently include measurements of FPG, HbA 1c and other blood markers [15,25,29]. After revising the diagnostic criteria for type 2 diabetes by introducing HbA 1c in 2010 [30], the ADA published guidelines and recommendations for diagnosing diabetes based on published data or derived from expert consensus [31].…”
Section: Introductionmentioning
confidence: 99%
“…In the multiethnic Atherosclerosis Risk in Communities (ARIC) [22]. Figure 1 and ESM Table 2 show that the separate addition of fasting glucose, HbA 1c or 2 h glucose to basic models with non-invasive variables leads to a strong increase in model accuracy [18,24,[36][37][38]. In several studies, HbA 1c improved the predictive power to a similar extent to fasting glucose.…”
Section: Prediction Models With Established Non-invasive and Conventmentioning
confidence: 97%